2022
DOI: 10.1002/hsr2.659
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus and associated risk factors among adults patients at Dessie referral and Kemise general hospitals in northeastern Ethiopia

Abstract: Background and Aims: Hepatitis is an inflammation of the liver that can reason a variety of health problems and can be fatal. According to the most recent estimates of the Global Burden of Disease study and WHO, viral hepatitis is accountable for around 1.34 million deaths yearly, which is comparable to the yearly number of deaths from HIV/AIDS (1.3 million), malaria (0.9 million), and tuberculosis (1.3 million). This study aimed to assess the prevalence of the Hepatitis B virus and associated risk factors amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The family history of HBV was also significantly associated with HBV infection. This is in line with similar studies reported from Ethiopia [ 5 , 35 , 41 , 42 ], Egypt [ 6 ], Rwanda [ 46 ], and South Brazil [ 44 ]. This might be due to a lack of understuding about HBVtransmission methods and, the sharing of different personal and household items within the family, vertical transmission, and unsafe sexual practices.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The family history of HBV was also significantly associated with HBV infection. This is in line with similar studies reported from Ethiopia [ 5 , 35 , 41 , 42 ], Egypt [ 6 ], Rwanda [ 46 ], and South Brazil [ 44 ]. This might be due to a lack of understuding about HBVtransmission methods and, the sharing of different personal and household items within the family, vertical transmission, and unsafe sexual practices.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to studies in Ethiopia [ 22 , 33 ] and Nigeria [ 34 ], indicating that socio-demographic characteristics were not risk factors for HBsAg positivity. On the contrary, other studies in Ethiopia [ 26 , 35 ], Eritrea [ 19 ], Sudan [ 36 ], Cameroon [ 37 ], and Thailand [ 38 ] found a significant association between socio-demographic factors, such as marital status, age, occupation, religion, and HBV infection.…”
Section: Discussionmentioning
confidence: 86%
“…Religion and marital status were not significantly associated with attitude of HBV infection. A similar study was conducted to assess the Prevalence of HBV and associated risk factors among adult patients at Dessie referral and Kemise general hospitals in northeastern Ethiopia [49].…”
Section: Discussionmentioning
confidence: 99%
“…The initial prevalence . We retrieved age-based HBV seroprevalence from Mohammed et al (2022) (9), who explored HBV infections in two Ethiopian hospitals.…”
Section: Methodsmentioning
confidence: 99%